Pendampingan Manajemen Usaha Pada Unit Usaha Mahasiwa Program Studi Bisnis Digital Institut Teknologi dan Bisnis Muhammadiyah Bali - Munawir, Munawir; Sri Sulistyawati, Upik; Umar Rofi'i, Yulianto; Allena Dewi, Shanti; Faturohman, Maman (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This community service aims to provide business management assistance to the business units of students of the Digital Business Study Program at the Muhammadiyah Bali Institute of Technology and Business which will be held from 13 to 15 December 2023. Mentoring participants are students of the Digital Business Study Program of the Muhammadiyah Bali Institute of Technology and Business and representatives from other study programs accompanied by lecturers from the Digital Business Study Program and Entrepreneurship Study Program. The method used in this service activity is training and mentoring to student business units. The results of the service found that the mentoring training participants were very concerned about efforts to improve their business and develop it. The role of the team in assisting requires effort and time to develop them to be competitive in their products. Mentoring training formulates future follow-up plans through regular meeting plans to discuss progress, challenges, and improvements that need to be made and schedule individual consultation sessions to discuss specific problems or needs faced by student unit managers.